Pengembangan Kerjasama Profesional Program Bimbingan dan Konseling - Arina Mufrihah; Rusmiyati; Nur Erlinasari (Institut Agama Islam Neegri Madura, 2021)
Aims of this descriptive qualitative research are organizing cooperational models of guidance and counseling and analizing use of those professional cooperation activities between counselor and other professionals for students as targeting subject of guidance and counseling service. Author got the needed data from observation method, interview method, and documentation method, while subject of this research are guidance and counseling teachers and students. Guidance and counseling teachers have created some cooperational patterns with motivator, psychology institution, college, and alumna. By these cooperational programs, students acknowledged that they got many supports in understanding and developing their potentials, coping their obstacles, and programming their individual planning. Penelitian ini merupakan penelitian deskriptif kualitatif dengan tujuan mengorganisasikan pola-pola kerjasama bimbingan dan konseling dan menelaah manfaat yang diperoleh siswa sebagai subjek sasaran layanan BK dari kegiatan kerjasama profesional antara konselor dengan pihak-pihak profesional lainnya. Data penulis peroleh dari observasi, wawwancara, dan dokumentasi, subjek dalam penelitian ini adalah Guru BK dan siswa. Penulis memperoleh hasil penelitian berupa pola kerjasama yang dijalin oleh tenaga BK ialah dengan: (1) motivator; (2) lembaga psikologi; (3) perguruan tinggi; dan (4) alumni. Dengan program kerjasama tersebut siswa mengakui banyak terbantu dalam memahami-mengembangkan potensinya, mengatasi hambatannya, dan melakukan perencanaan individual.